Coronavirus disease 2019 and sudden sensorineural hearing loss. Issue 11 (1st November 2020) - Lang, B; Hintze, J; Conlon, B
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 emerged in December 2019 in Wuhan, China, and was declared a global health emergency of international concern by the World Health Organization on 30th January 2020. It has resulted in almost 600 000 deaths to date worldwide. Sudden sensorineural hearing loss is a known complication of a number of viral infections, but there is little in the literature to date on its association with coronavirus disease 2019. Case report: This paper presents the case of a 30-year-old female staff nurse who contracted coronavirus disease 2019 and presented to our department with a significant unilateral sensorineural hearing loss confirmed on audiogram. She was treated with a course of oral steroids, but unfortunately there was no improvement in her hearing. Conclusion: This case report is important as it highlights the importance of having a low index of suspicion when patients present with a variety of symptoms not previously associated with coronavirus disease 2019. The paper also discusses the controversy surrounding the use of steroids in the management of this disease.